2014
DOI: 10.1111/pace.12545
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Quadripolar Left Ventricular Leads Improves the Hemodynamic Response to Cardiac Resynchronization Therapy

Abstract: The quadripolar LV lead was associated with a better hemodynamic response and higher CRT responder rates when compared with unipolar-simulated and bipolar LV leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Initial experience has shown that CRT using quadripolar leads with an optimized left ventricular pacing configuration (LVPC) improved acute hemodynamics, synchrony, and also hospitalization rate. [ 5 , 6 ] Moreover, the method of improving the CRT response by multipoint left-ventricular pacing (MultiPoint Pacing [MPP]; St Jude Medical, Sylmar, CA), which recruits more left ventricular volume of myocardium at the same time based on LV quadripolar leads, has been confirmed by clinical practice. [ 7 ] Forleo et al have demonstrated that MPP improves clinical status and leads to an extra increase in LV ejection fraction (LVEF) compared with conventional CRT.…”
Section: Introductionmentioning
confidence: 99%
“…Initial experience has shown that CRT using quadripolar leads with an optimized left ventricular pacing configuration (LVPC) improved acute hemodynamics, synchrony, and also hospitalization rate. [ 5 , 6 ] Moreover, the method of improving the CRT response by multipoint left-ventricular pacing (MultiPoint Pacing [MPP]; St Jude Medical, Sylmar, CA), which recruits more left ventricular volume of myocardium at the same time based on LV quadripolar leads, has been confirmed by clinical practice. [ 7 ] Forleo et al have demonstrated that MPP improves clinical status and leads to an extra increase in LV ejection fraction (LVEF) compared with conventional CRT.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, quadripolar leads have been introduced. While serving to address high pacing thresholds and phrenic nerve stimulation issues, the multiple pacing configurations can also result in better hemodynamic response than standard, distal biventricular stimulation . Using bioimpedance, Osca et al .…”
Section: Discussionmentioning
confidence: 99%
“…While serving to address high pacing thresholds and phrenic nerve stimulation issues, 16 the multiple pacing configurations can also result in better hemodynamic response than standard, distal biventricular stimulation. 9,17 Using bioimpedance, Osca et al 9 showed that the highest cardiac index was obtained by pacing from one of the two proximal electrodes, associated with AV and VV delay optimization, in 56% of patients. In their study, nine AV delays then seven VV delays were tested for each of the four electrodes, resulting in 64 settings tested, which is probably impractical in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel quadripolar LV leads offer 10 LV pacing configurations, and unipolar (extended bipolar) LV pacing is widely used to overcome technical issues such as phrenic nerve capture and stimulation thresholds. Using the best individual pacing configuration for each patient improves the hemodynamic response to CRT ( 7 - 9 ). Although the impact of LV pacing polarity on contractile functions has been investigated, little is known about the role of pacing polarity on repolarization patterns ( 10 ).…”
Section: Introductionmentioning
confidence: 99%